Corporate Social Responsibility and customer satisfaction : the case of Islamic banks in Palestine - Sayed Ahmed, Nael Y. M.
Islamic banks play a major role in solving many financial and social problems. Corporate Social Responsibility (CSR) has become a very important concept that is practiced by Islamic banks worldwide to show better corporate image. The current study focuses on the CSR disclosures of Islamic banks operating in Palestine, and customers' perception with CSR practices of these banks. The study has three main objectives. Firstly, it aims to measure the quality of Corporate Social Responsibility Disclosure (CSRD) of Islamic banks in Palestine within 2008-2013. Secondly, to measure the level of customers' perception of CSR practices of Islamic banks in Palestine. And finally, to explain the differences between Palestinian Islamic banks' CSRD and the customers' perception of CSR practices. The data was based on secondary data (using annual reports of Islamic banks during 2008-2013) and primary data (i.e. questionnaires and interviews). The study used mixed methodology. Content analysis was used to measure the quality and trend of CSRD, while questionnaires were used to measure customers perception, and finally interviews were conducted to further enhance the discussion of the results from the analysis. The study found that overall; CSRD improved between 2008 and 2013. This was true for five out of the seven dimensions of CSRD (i.e. Environment, Corporate Governance, Stakeholders engagement, research and development, and Products and services). The results also revealed that customers were moderately satisfied (3.97) with CSR practices of Islamic banks in Palestine. The demographics of questionnaire respondents showed mixed results. Age, years of experience, level of education, bank type, and customer income had no differences, whereas gender and bank name affected customer' perception on CSR practices in the area of products and services. The findings also showed that Islamic banks and customers have to work together to promote awareness about CSR in general, and that Islamic banks need to promote Shari'ah compliance and charity among stakeholders in order to gain an edge over competitors within the financial sector. The findings also showed that mandatory CSRD did not significantly improve during 2008-2013, whereas it significantly improved for voluntary CSRD. The current study suggested increasing CSRD, which are more relevant to customers, such as products and services, research and development, and corporate governance. The study also encouraged future research in Palestine using larger data sources in order to gain a comprehensive view of the topic, as the industry is young and small compared to similar industries in other countries.